Base Metal Catalyzed Isocyanide Insertions. Issue 2 (4th October 2019) - Collet, Jurriën W.; Roose, Thomas R.; Ruijter, Eelco; Maes, Bert U. W.; Orru, Romano V. A.
Abstract: Isocyanides are diverse C1 building blocks considering their potential to react with nucleophiles, electrophiles, and radicals. Therefore, perhaps not surprisingly, isocyanides are highly valuable as inputs for multicomponent reactions (MCRs) and other one‐pot cascade processes. In the field of organometallic chemistry, isocyanides typically serve as ligands for transition metals. The coordination of isocyanides to metal centers alters the electronic distribution of the isocyano moiety, and reaction pathways can therefore be accessed that are not possible in the absence of the metal. The tunable reactivity of the isocyanide functional group by transition metals has evolved into numerous useful applications. Especially palladium‐catalyzed isocyanide insertion processes have emerged as powerful reactions in the past decade. However, reports on the use of earth‐abundant and cheap base metals in these types of transformations are scarce and have received far less attention. In this Minireview, we focus on these emerging base metal catalyzed reactions and highlight their potential in synthetic organic chemistry. Although mechanistic studies are still scarce, we discuss distinct proposed catalytic cycles and categorize the literature according to 1) the (hetero)atom bound to and 2) the type of bonding with the transition metal in which the (formal) insertion occurs. Abstract : Back to basics : Base metal catalyzed processes involving isocyanide insertion have recently evolved as promising cross‐coupling reactions. While mechanistic studies are still scarce, proposed catalytic cycles are discussed in this Minireview and the literature is categorized accordingly. This should facilitate the development of new processes to efficiently assemble high added‐value compounds.